2014
DOI: 10.1155/2014/483760
|View full text |Cite
|
Sign up to set email alerts
|

Caries Distribution, Prevalence, and Treatment Needs among 12–15-Year-Old Secondary School Students in Port Harcourt, Rivers State, Nigeria

Abstract: Objective. There is a change in the trends and distribution of dental caries in established and nonestablished market economies. The aim of this study was to describe caries distribution, prevalence, and treatment needs among school children in Port Harcourt, Nigeria.Materials and Methods. The study was a cross-sectional survey of students between the ages of 12 and 15 years. Data was collected using a structured questionnaire and clinical oral examination. Analysis of data was done using statistical package f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 15 publications
2
44
2
Order By: Relevance
“…e carious lesions were significantly more prevalent in the second molars compared to the first molars, which corroborates with studies from African populations [22,[26][27][28]. In contrast, other studies [23,29,30] from developing countries reported the first molars to be more frequently involved with caries compared to the second molars. Various reasons have been proposed for the differing caries susceptibilities of teeth including tooth anatomical features, eruption times, posteruptive enamel maturation of the surfaces, and the individual's age of exposure to high cariogenic diet [31,32].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…e carious lesions were significantly more prevalent in the second molars compared to the first molars, which corroborates with studies from African populations [22,[26][27][28]. In contrast, other studies [23,29,30] from developing countries reported the first molars to be more frequently involved with caries compared to the second molars. Various reasons have been proposed for the differing caries susceptibilities of teeth including tooth anatomical features, eruption times, posteruptive enamel maturation of the surfaces, and the individual's age of exposure to high cariogenic diet [31,32].…”
Section: Discussionsupporting
confidence: 86%
“…Overall, decayed teeth were more prevalent in the mandible than the maxillae though the difference was not statistically significant. is finding is contrary to previous reports that observed significant differences between the two dental arches [22][23][24]. We recorded significantly more molars with decay compared to all the other teeth ( Figure 1) in support of previous studies [22,25].…”
Section: Discussioncontrasting
confidence: 56%
“…Access to oral health care in Nigeria is poor [1] and efforts made to improve access to oral health care in Nigeria have been largely unsuccessful [2]. Poor integration of oral health into general health has been the bane of the Nigerian health system despite the seeming progress in oral health evidenced by the introduction of the 2012 Oral health policy [2].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies found that the system falls short of many desirable attribute. These studies show that the health system, is neither efficient nor effective thus available resources in many areas, are overstretched and grossly inadequate (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this being that the little resources assigned to the health sector are mainly directed towards life-threatening conditions such as HIV/AIDS, tuberculosis, and malaria rather than dental caries and other oral diseases (12,13). In addition the strategies to improve access documented in the countries oral health policy is yet to be fully implemented (1,13,14).…”
Section: Introductionmentioning
confidence: 99%